Implementation of the Independent Campus Learning Policy ”MBKM”: An Overview from the Perspectives of Students and Lecturers - Syahruddin; Tambaip, Beatus (Journal of Education Reseach and Evaluation, 2023)
The Freedom to Learn the Independent Campus Policy (MBKM) is an Indonesian government initiative that aims to encourage innovation in higher education and give students freedom to choose courses, colleges and learning methods that suit their interests, talents and needs. This study aims to evaluate the implementation of the MBKM policy at University, as well as explore the perspectives of students and lecturers regarding the implementation of the policy. The research method used is a qualitative approach with data collection techniques through in-depth interviews and participatory observation. The respondents of this study consisted of 317 students who had participated in the MBKM program and 18 lecturers who were involved in implementing the policy. Data analysis was carried out through the coding stage and the themes that emerged from the interviews and data triangulation with observation. The results showed that the implementation of the MBKM policy at University had a significant impact on students and lecturers. From a student perspective, the MBKM policy gives them the freedom to choose courses, access learning resources, and participate in extracurricular activities according to their interests and talents. From the perspective of lecturers, the MBKM policy requires changes in teaching and mentoring approaches. Overall, the evaluation of the implementation of the MBKM policy at University shows significant benefits for students and lecturers. However, there are also challenges that need to be overcome, such as managing student time and adjusting lecturer teaching approaches.